PENGEMBANGAN DAN PELATIHAN DIVERSIFIKASI PRODUK OLAHAN PEPAYA DENGAN MEMANFAATKAN POTENSI DESA UNTUK MENINGKATKAN KESEJAHTERAAN EKONOMI - Heni Safitri; Aris Sanjaya (Jurnal Buletin Al-Ribaath, 2018)
The development of diversification of local food processing is seen as strategic in supporting the creation and development of productive economic enterprises. One of the agricultural potentials in Ambawang Kuala Village that can be developed is papaya fruit. Besides being able to be processed into papaya extract and dodol, papaya can also be processed into papaya chips with various flavors. The basic problem is the lack of processing of existing resources into other products that are more attractive and durable. The method used to carry out this service activity is direct socialization and practice. Basically all activities that have been carried out are expected to be able to provide benefits to the society in the Village and help the development of Small and Medium Enterprises (MSMEs) in Ambawang Kuala Village.